Human resource management practices of school heads - Aquino, Desiree Anne Lorraine B.; Capacio, Leadean Jay; Naparan, Genesis B. (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This Qualitative Multiple Case Study was conducted to explore teachers’ experiences under the Human Resource Management practices of school heads. Selected elementary school teachers from public and private schools, and their school heads from Pagadian City Division were interviewed. This study has emerged from the major components Human Resource Management Practices, Challenges, and Coping Mechanisms of School Heads during the first Emergency School Years. Based on the components they experienced under their school heads, they were provided a clear picture of teachers’ tasks or activities, planned for the school in general, managed their workloads, listened to teachers’ voices, offered technical assistance, considered teachers’ emergency excuses, realigned budget for teachers’ supply and find means to support teachers. However, the school head also faced challenges such as communication due to the parade of tasks and insufficient resources for module printing. Nevertheless, they were able to solve these challenges. Different modalities call for different tasks, different tasks demand different preparations, different preparations advance to level of operations. School Heads resilient attitude toward the goal of negating these uncontrollable stretches and putting colleagues’ contexts on top of decision making save the day.